Conductive and Inductive Coupling between Faulted Power Lines and Buried Pipeline by Considering the Effect of Soil Structure - Ali I. El Gayar; Zulkurnain Abdul-Malek; Mohammed Imran M; Chin Leong Wooi; Ibtihal Fawzi Elshami (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The AC total interference of faulted power lines to gas pipelines sharing the same right of way, which may pose a threat to operating personnel and equipment, was studied. The main advantage of this work is to determine the effects of different soil structures on the induced voltage for various soil resistivities. Two main approaches were used to compute the induced voltages, namely the method of moment (MOM), which is based on electromagnetic field theory, and the circuit based method, which uses the circuit grounding analysis to compute the conductive interference and the circuit based models to compute the inductive interference. A 10-km-long parallel pipeline-transmission line model was developed. The soil resistivity was varied, and the induced voltages obtained from both approaches were compared. Soil resistivity and soil structure are important parameters that affect the AC interference level. The results of the study show that the earth potentials and the metal GPRS are independent. Higher soil resistivity causes the tower ground resistance to increase, thus making the shield wire’s attractiveness as a fault current return path to increase, which in turn forces the induced net EMF and the cumulative GPR in the pipeline to reduce.